Inklusivisme Maqâsid Syarî’ah Menuju Pembangunan Berkelanjutan Bank Syariah di Indonesia - Budi Sukardi (Universitas Darussalam Gontor, 2016)
This paper review to assess the performance of Islamic Bank of Devisa on syarî’ah maqâsid index and its inclusive contribution to sustainable development of Islamic Bank in Indonesia. This paper was an exploratory study with survey eksperience, using the analysis of secondary datas and the pilot studies of the population of Islamic Bank in Indonesia with sample of Islamic Bank of Devisa, such as Bank Muamalat Indonesia, BNI Syariah, Bank Syariah Mandiri, and Bank Syariah Mega Indonesia. Research lowered concept of maqâsid syarî’ah index into three main dimensions; individual education, establishing justice and the public interest. The results showed the syarî’ah maqâsid index of Islamic Bank of Devisa in 2012-2014; Bank Muamalat Indonesia scored of 24,9209, Bank Syariah Mandiri scored of 25.4773, Bank Negara Indonesia Syariah scored of 25.6511 and Bank Mega Syariah Indonesia scored of 16.5110. The inclusive contribution of maqâṣid syarî’ah to sustainable development Islamic Bank in Indonesia is an attempt to reduce the lack of access to financial services, such as providing access to the community and a focus on risk sharing and redistribution of wealth. Islamic financial innovation needed to provide appropriate products and financial services for the community to increase their income and social welfare. Their access to financial services for the sustainability of economic, environmental and religious order Islamic Bank can contribute to the public and become a leading industry in achieving the highest aim of sharia-focused and oriented to the survival of human, natural, economic resources creative, and all aspects of life.